2009
DOI: 10.2337/db08-0263
|View full text |Cite
|
Sign up to set email alerts
|

Physical Inactivity Differentially Alters Dietary Oleate and Palmitate Trafficking

Abstract: 1OBJECTIVE-Obesity and diabetes are characterized by the incapacity to use fat as fuel. We hypothesized that this reduced fat oxidation is secondary to a sedentary lifestyle. RESEARCH DESIGN AND METHODS-We investigated the effect of a 2-month bed rest on the dietary oleate and palmitate trafficking in lean women (control group, n ϭ 8) and the effect of concomitant resistance/aerobic exercise training as a countermeasure (exercise group, n ϭ 8). Trafficking of stable isotope-labeled dietary fats was combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
110
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 55 publications
8
110
0
Order By: Relevance
“…Until now, most studies have focused on palmitate and its involvement in intramuscular ceramide accumulation and induction of insulin resistance (1,19,53,64), the rationale being that it can form both the sphingoid backbone (dhSph, through condensation of palmitoyl-CoA and L-serine by sarcoplasmic SPT) and palmitoyl-ceramide (through the activity of sarcoplasmic ceramide synthase), thus increasing ceramide content by two parallel mechanisms. Palmitate, but not oleate, was shown to increase ceramide accumulation in muscle myotubes (11), decrease phosphorylation of Akt (55), and induce muscle insulin resistance (52), the latter even improving palmitate-induced insulin resistance (6,14,55). On the contrary, a study by Thompson et al (69) reported that oleate and linoleate were more potent inhibitors of insulin-stimulated glucose uptake, glucose phosphorylation, and glycogen synthesis in isolated soleus muscle than palmitate.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, most studies have focused on palmitate and its involvement in intramuscular ceramide accumulation and induction of insulin resistance (1,19,53,64), the rationale being that it can form both the sphingoid backbone (dhSph, through condensation of palmitoyl-CoA and L-serine by sarcoplasmic SPT) and palmitoyl-ceramide (through the activity of sarcoplasmic ceramide synthase), thus increasing ceramide content by two parallel mechanisms. Palmitate, but not oleate, was shown to increase ceramide accumulation in muscle myotubes (11), decrease phosphorylation of Akt (55), and induce muscle insulin resistance (52), the latter even improving palmitate-induced insulin resistance (6,14,55). On the contrary, a study by Thompson et al (69) reported that oleate and linoleate were more potent inhibitors of insulin-stimulated glucose uptake, glucose phosphorylation, and glycogen synthesis in isolated soleus muscle than palmitate.…”
Section: Discussionmentioning
confidence: 99%
“…Although oleate and palmitate have been shown to be similarly taken up and oxidized in human myocardium (18), their use in the whole body and skeletal muscle in humans has shown some notable differences (19)(20)(21)(22). Because dietary oleate (18:1) is preferentially oxidized relative to palmitate (16:0) and stearate (18:0) (22), we anticipated that an oleic acid analog of 18 F-FTP might show a higher specificity for mitochondrial FAO than 18 F-FTP itself.…”
mentioning
confidence: 99%
“…One-way ANOVA was also used to compare the model parameters, which were k (rate constant) and maximum percent recovery of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetate among the three conditions. A repeated-measures ANOVA was used to compare [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]palmitate versus [9, H] palmitate oxidation time courses within each condition.…”
Section: Downloaded Frommentioning
confidence: 99%
“…A repeated-measures ANOVA was used to compare [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]palmitate versus [9, H] palmitate oxidation time courses within each condition. Tukey post hoc test was used to locate signifi cant differences.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation